Republic of Madagascar : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2021)
At the request of the Ministry of Economy and Finance (MEF) and in consultation with the Africa Department (AFR) of the International Monetary Fund (IMF), a remote Government Finance Statistics (GFS) mission from the Statistics Department (STA) took place in Madagascar from October 26 to November 13, 2020. The objective of this mission was to continue supporting the authorities in their project to adopt international GFS standards based on the methodology of the Government Finance Statistics Manual 2014 (GFSM 2014) and the Public Sector Debt Statistics Guide (PSDSG) and to improve GFS in general.